PROMOTING INTRA-FIRM TRANSFER OF KNOWLEDGE THROUGH COMPETITION AND SHARING A Field Study - Jermias, Johnny (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
This paper examines three main concerns about intra-firm transfer on knowledge in the management accounting and strategic management literature: the ability of real-world organizations to learn productively, the levels of aggregation in which the productive learning occurs, and the types of management interventions that are both desirable and productive. Based on a field study conducted in several business units of a multinational corporation, this paper reports how management makes conscious andsystematic efforts to transform ideas from the best practice within the company as well as from its competitors.The company uses Management By Olympic Systems to accelerate learning through competition and sharing. The system utilizes Olympic principles and integrates individual and team concepts to achieve the Olympic targets. A broad range of Olympic targets in terms of financial and non-financial linked to the companyâs incentive systems is used to improve business operations, to motivate managers and employees, and to meet stakeholdersâ expectations.